Locus of control, adjustment, and aspirationf of adolescent boys of Bacolod Boy's Home Foundation, Inc. - Majaducon, Maria Jeryka C. (2016.)
This study was conducted to determine the circumstances that brought selected adolescents in Bacolod Boy's Home Foundation, Inc. their locus in control, psychosocial adjustments, occupational and educational aspirations. Descriptive analysis showed that participants exhibited external locus of control because of the harsh condition they experienced in the past like living in extreme poverty and receiving physical punishment from their parents or guardians. Content analysis showed that participants where either forced or personally volunteered to be admitted to the institution. This require psycho-socio adjustments in ralation with the rules and regulations, duties and responsibilities, peers and staff. However, with time and guidance, they developed ways to overcome these difficulties. In terms of aspirations, participants aimed to obtain college degree to be able to find immediate employment. Most of them aimed for jobs which are service-oriented, science related and technicians works.
Research Project -- Bacheolor of Arts (Psychology). University of the Philippines Visayas, Iloilo.
2016.
Keywords: Adolescence -- Boys; Bacolod Boy's Home Foundation, Inc